2001
DOI: 10.1523/jneurosci.21-06-02067.2001
|View full text |Cite
|
Sign up to set email alerts
|

The Primate Amygdala Mediates Acute Fear But Not the Behavioral and Physiological Components of Anxious Temperament

Abstract: Temperamentally anxious individuals can be identified in childhood and are at risk to develop anxiety and depressive disorders. In addition, these individuals tend to have extreme asymmetric right prefrontal brain activity. Although common and clinically important, little is known about the pathophysiology of anxious temperament. Regardless, indirect evidence from rodent studies and difficult to interpret primate studies is used to support the hypothesis that the amygdala plays a central role. In previous stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
177
8
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(209 citation statements)
references
References 35 publications
23
177
8
1
Order By: Relevance
“…Consistent with these population-based findings, experimental work has shown that prepared stimuli elicit increased arousal and preferential attention relative to neutral stimuli (for review, see Ohman and Mineka (2001)). Neurobiologically, their effects are thought to be mediated by the amygdala as well as the orbitofrontal cortex (Meunier et al 1999;Kalin et al 2001;Murray and Izquierdo 2007). Our quantitative models reveal that discriminative fear conditioning occurred faster when humans were exposed to images of snakes or spiders than when they were exposed to images of abstract fractals, replicating prior work (Ho and Lipp 2014).…”
supporting
confidence: 83%
See 2 more Smart Citations
“…Consistent with these population-based findings, experimental work has shown that prepared stimuli elicit increased arousal and preferential attention relative to neutral stimuli (for review, see Ohman and Mineka (2001)). Neurobiologically, their effects are thought to be mediated by the amygdala as well as the orbitofrontal cortex (Meunier et al 1999;Kalin et al 2001;Murray and Izquierdo 2007). Our quantitative models reveal that discriminative fear conditioning occurred faster when humans were exposed to images of snakes or spiders than when they were exposed to images of abstract fractals, replicating prior work (Ho and Lipp 2014).…”
supporting
confidence: 83%
“…Relative to fearirrelevant stimuli (e.g., flowers, mushrooms), fear-relevant stimuli have been shown to facilitate classical conditioning (Ho and Lipp 2014) and slow extinction learning (Fredrikson et al 1976; Ohman et al 1975a,b). Work in nonhuman primates suggests that innate responses to fear-relevant stimuli are mediated by the amygdala and orbitofrontal cortex (Meunier et al 1999;Kalin et al 2001;Murray and Izquierdo 2007). These structures play crucial roles in fear acquisition (Davis 1992; Maren 2001), extinction (Schiller andDelgado 2010;Milad and Quirk 2012), and value-based learning (Schoenbaum et al 1998;Holland and Gallagher 2004), and thus their preferential recruitment by prepared stimuli might enhance dynamic aversive learning.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We believe this evidence suggests that heightened affiliative social interactions following amygdala lesions stems from a more general inability to properly perceive danger or threat in the environment and use such information to modulate social behavior adaptively. In line with this view, deficits in threat detection or fear reactivity have been specifically demonstrated for monkeys with bilateral neurotoxic amygdala lesions in both social (Machado & Bachevalier, 2006) and nonsocial settings (Izquierdo, Suda, & Murray, 2005;Kalin, Shelton, & Davidson, 2004;Kalin, Shelton, Davidson, & Kelley, 2001;Mason et al, 2006;Meunier, Bachevalier, Murray, Málková, & Mishkin, 1999). These abnormalities are not restricted to nonhuman primates, since humans with amygdala lesions also demonstrate specific deficits in identifying fearful facial expressions (Adolphs et al, 1999), rating the magnitude of fearful expressions (Adolphs, Tranel, Damasio, & Damasio, 1995) and assessing the approachability or trustworthiness of unfamiliar individuals (Adolphs, Tranel, & Damasio, 1998).…”
Section: Social Disinhibition Persists Across Contextsmentioning
confidence: 80%
“…One tool that might be used to investigate this issue relies on monkeys' innate emotional responses to snakes. Macaques, even snake-naive ones, exhibit marked defensive responses in the presence of fake or real snakes (Mineka, 1987;Nelson et al, 2003), and elicitation of these responses requires an intact amygdala (Aggleton and Passingham, 1981;Meunier et al, 1999, Kalin et al, 2001. Another commonly used tool relies on monkeys responses to an unfamiliar human observer.…”
Section: Introductionmentioning
confidence: 99%